Deciphering the molecular functions of sterols in cellulose biosynthesis - Schrick, Kathrin; DeBolt, Seth; Bulone, Vincent (My University, 2013)
Sterols play vital roles in plant growth and development, as components of membranes and as precursors to steroid hormones. Analysis of Arabidopsis mutants indicates that sterol composition is crucial for cellulose biosynthesis. Sterols are widespread in the plasma membrane (PM), suggesting a possible link between sterols and the multimeric cellulose synthase complex. In one possible scenario, molecular interactions in sterol-rich PM microdomains or another form of sterol-dependent membrane scaffolding may be critical for maintaining the correct subcellular localization, structural integrity and/or activity of the cellulose synthase machinery. Another possible link may be through steryl glucosides, which could act as primers for the attachment of glucose monomers during the synthesis of β−(1 → 4) glucan chains that form the cellulose microfibrils. This mini-review examines genetic and biochemical data supporting the link between sterols and cellulose biosynthesis in cell wall formation and explores potential approaches to elucidate the mechanism of this association.
Keywords: Sterols; Steryl glucosides; Cellulose; Plasma membrane microdomains; Lipid rafts; Cell wall